Pembentukan Perpustakaan untuk Meningkatkan Literasi di Kalangan Santri Rumah Tahfidz Nurul Ilmi 316 - Endang Heriyani (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
According to Article 1 paragraph (4) of the National Education System Law Number 20 of 2003, education is carried out by developing a culture of reading, writing, and arithmetic. The habits of reading and writing are very important activities. The habit of reading can be practiced if books are available. In addition to participating in Al-Quran learning activities, students at Nurul Ilmi 316 Quran Memorization Center also attend formal education outside the boarding school. Some attend elementary school, junior high school, or high school. On Saturdays and Sundays, schools are closed, so students have a lot of free time. This free time needs to be used for useful activities. One activity that can be done is reading books that contain a wealth of knowledge. For this reason, a library is needed. The challenge faced by Quran memorization centers in general, including Nurul Ilmi 316 Quran Memorization Center, is the lack of supporting literacy facilities, namely a library. This community service program aims to improve literacy among students at the Nurul Ilmi 316 Quran Memorization Center through the establishment of a library. The methods used in this program are observation, planning, and implementation. The conclusion of this community service is that the establishment of a library can improve literacy among students at Nurul Ilmi 316 Quran Memorization Center. With increased literacy, it is hoped that academic achievement at school will also improve. The library is an important facility in supporting the educational process, shaping the character of students, and encouraging the formation of an intelligent, noble-minded Quranic generation that will serve as the successor to the nation's struggle.